"FUNKY SLAWE" IN THE CREATIVE PROCESS OF SENDRATASIK (ART, DRAMA, DANCE, MUSIC) STUDENTS IN THE UNIVERSITY OF PGRI PALEMBANG - Rio Eka Putra; Muhsin Ilhaq (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2019)
Traditional music of terbangan from Palembang city is composed into the composition of new music. It's hoped that this music can be accepted by all circle whether it's old people or young ones. This process involved several art students especially the students of art, drama, dance, music department in the university of PGRI Palembang. The achievement of this art development is that the students obtain the science of composing traditional music and maintaining the tradition of terbangan. The variable of this applied research used the approach of popular music. This composition style has extensive attraction, tends to have many audiences, and is distributed to the public. From the results of this research, it's hoped new creative ideas in the development of traditional music and unique ideas in packaging this new development that have quality in maintaining local image and wisdom appear in the society.Development; Traditional art; New music composition